2020
DOI: 10.3892/etm.2020.8505
|View full text |Cite
|
Sign up to set email alerts
|

Decreased basal and stimulated salivary parameters by histopathological lesions and secretory dysfunction of parotid and submandibular glands in rats with type�2 diabetes

Abstract: Patients with type 2 diabetes mellitus (T2DM) present with dry mouth, polydipsia and taste impairment due to salivary secretion disorder. However, the underlying functional mechanism of T2DM remains unknown. The present study found that T2DM rats had significantly lower salivary flow rate and salivary alpha amylase activity, and attenuated salivary secretion responses to acid stimulation compared with control rats. Histopathological observation found that T2DM rats had inflammatory cell infiltration with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(28 reference statements)
2
10
0
1
Order By: Relevance
“…We showed that STZ injection promoted degenerative changes in the form of vacuolations in both acinar and ductal cells of parotid gland. These results were consistent with previous studies demonstrating that diabetes likely induces morphological alterations in salivary glands that are of a lipid nature as they are removed during the fixation and processing of the samples [ 10 , 11 , 13 , 16 – 18 ]. In diabetes, vacuolations are more evident in the parotid gland than in the submandibular glands [ 10 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We showed that STZ injection promoted degenerative changes in the form of vacuolations in both acinar and ductal cells of parotid gland. These results were consistent with previous studies demonstrating that diabetes likely induces morphological alterations in salivary glands that are of a lipid nature as they are removed during the fixation and processing of the samples [ 10 , 11 , 13 , 16 – 18 ]. In diabetes, vacuolations are more evident in the parotid gland than in the submandibular glands [ 10 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The majority of oral changes related to salivary gland dysfunction are characterised by hyposalivation and xerostomia, which significantly reduce the quality of life in patients with diabetes [ 5 7 ]. Both basal and stimulated secretion of the parotid and submandibular glands are dramatically downregulated under prolonged hyperglycaemia in humans and rats [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that maternal type 1 diabetes induced postnatal changes in the development of rat SG in offspring, including decreased AQP5 expression [ 126 ]. Rats with type 2 diabetes displayed decreased saliva flow, inflammatory cell infiltration of SG and decreased AQP5 expression [ 127 ]. Further studies are required to fully assess the role of AQP5 in diabetic xerostomia.…”
Section: Involvement Of Aqps In Sg Pathologiesmentioning
confidence: 99%
“…AQP5 is also downregulated in the parotid salivary gland of T2D rats that showed decreased salivary flow rate [ 138 ]. Rats treatment with bone marrow-derived stem cells improves the salivary flow rate and alters AQP5 levels in the parotid gland [ 139 ].…”
Section: Possible Role Of Aqps “Metabolic Network” In Obesity-induced Systemic Insulin Resistancementioning
confidence: 99%